PENGARUH KELENGKAPAN PRODUK, KUALITAS PELAYANAN DAN STORE ATMOSPHERE TERHADAP MINAT BELI ULANG KONSUMEN PADA TOKO GROSIR NICKS MARKET DI DESA LODTUNDUH, KECAMATAN UBUD, KABUPATEN GIANYAR. - Ni Komang Ayu Apri Intansari; I Nengah Suardhika (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2025)
The existence of retail businesses makes it easier to distribute goods and services needed by the public or final buyers. The sustainability of a retail business is largely determined by customers' decisions in making repeat purchases. Product completeness is a crucial aspect that must be fulfilled by companies or retail stores so that consumers remain loyal and do not move elsewhere. Apart from that, service quality is also an essential factor that must be considered, because optimal service will provide a sense of comfort and convenience for customers when shopping. An attractive store atmosphere is able to create a positive impression in the minds of consumers, which in turn can increase their motivation to make repeat transactions. This study aims to evaluate the influence of product completeness, service quality and store atmosphere on customers' intention to make repeat purchases at the Nicks Market Gianyar wholesale store. The research population is consumers who have shopped at the Nicks Market grocery store. The sample for this research was 96 respondents who were determined based on purposive sampling techniques. This research collects data through distributing questionnaires which are then analyzed using the multiple linear regression method. The findings of this research show that product completeness, service quality, and store atmosphere each contribute to consumers' interest in making repeat purchases at the Nicks Market grocery store. For future research, it is recommended that this study be expanded to include other variables, such as location factors, level of customer satisfaction, pricing strategy, and perceptions of store image.